If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8b = -4 + 2(2 + 5b) 8b = -4 + (2 * 2 + 5b * 2) 8b = -4 + (4 + 10b) Combine like terms: -4 + 4 = 0 8b = 0 + 10b 8b = 10b Solving 8b = 10b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-10b' to each side of the equation. 8b + -10b = 10b + -10b Combine like terms: 8b + -10b = -2b -2b = 10b + -10b Combine like terms: 10b + -10b = 0 -2b = 0 Divide each side by '-2'. b = 0 Simplifying b = 0
| R+VR=7 | | 116-x=216 | | 0.1-0.01(x+1)=-0.01(1-x) | | .04x+.07(11000-x)=660 | | y=-24-x | | 8-2(x-6)=-7x | | 6=2x+-2 | | x=2ln(6-y)+3 | | 3x+2=-20+30 | | -3(1-5r)=9+3r | | .04x+.07(1000-x)=660 | | 4b+20=60 | | F(x)=2ln(6-x)+3 | | -2m-5(1-5m)=110 | | 5+(x-9)+x=59 | | F(x)=xsq+x | | 2(x+12)+7(x-5)=4x-56 | | (8x-y-7)(6x)= | | x^3=41 | | 5y+36=10y+6 | | 0=x^3-3x-6 | | 4(2r+5)=6(r-2) | | 9-11x-7-10x=5 | | 6.1-r=3.4 | | 24d+40de= | | 4(z-3)+z=-2 | | -3(y-4)=18 | | -(9x-9)+9x= | | -3(7+5n)=-96 | | -1/3(2b-6) | | 3+4x+3=-2 | | X(7x-3)=(7x+8)(x-1) |